Accountability for Error in Procedendo in Bankruptcy Proceedings in Indonesia - Julya Paulina Siburian; Duhita Driyah Suprapti; Anis Widyawati (Universitas Negeri Semarang, 2025)
This study aims to comprehensively analyze the forms of maladministration that give rise to error in procedendo in the adjudication of bankruptcy cases in Indonesia, and to evaluate the extent to which the principles of accountability and procedural justice are implemented by commercial court judges. Employing a normative legal research method through statutory, case-based, and conceptual approaches, this study examines the Central Jakarta Commercial Court Decision No. 226/Pdt.Sus-PKPU/2023 and the Supreme Court Decision No. 1103 K/Pdt.Sus-Pailit/2024 as the primary bases of analysis. The findings reveal various forms of maladministration, including delays in the cassation process, violations of statutory deadlines, inaccuracies in determining the legal standing of creditors and debtors, and irregularities in the creditor-verification process. These procedural deviations significantly undermine the effectiveness of the principles of expeditious, simple, and low-cost proceedings as mandated by Law No. 37 of 2004. Based on Romzek and Dubnick’s theory of accountability, the study finds that legal and bureaucratic accountability tend to predominate, while professional and political accountability remain suboptimal. Through the lens of Tom R. Tyler’s theory of procedural justice, the research asserts that judicial non-compliance with procedural requirements adversely affects public trust and the perception of fairness in commercial court proceedings. Accordingly, this study recommends strengthening internal oversight mechanisms, enhancing the professional capacity of judges, and ensuring consistent adherence to procedural standards to promote legal certainty and justice in Indonesian bankruptcy proceedings.